2018
DOI: 10.2106/jbjs.cc.17.00198
|View full text |Cite
|
Sign up to set email alerts
|

Snapping at the Lateral Aspect of the Elbow

Abstract: Snapping elbow is a phenomenon that often coincides with pain and limited function. Accurate diagnosis is critical because misdiagnosis has been demonstrated to have serious consequences, including the need for repeat surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Most of the surgical interventions were performed arthroscopically, also with the advantage of clarifying other intra-articular pathologies. Overall, the outcome results are good to excellent, although the authors critically note that no standardized outcome measures were used 3 , 4 , 8 , 10 . In particular, no functional scores were evaluated that included not only pain but also limited range of motion, the other main symptom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the surgical interventions were performed arthroscopically, also with the advantage of clarifying other intra-articular pathologies. Overall, the outcome results are good to excellent, although the authors critically note that no standardized outcome measures were used 3 , 4 , 8 , 10 . In particular, no functional scores were evaluated that included not only pain but also limited range of motion, the other main symptom.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, no functional scores were evaluated that included not only pain but also limited range of motion, the other main symptom. Some studies reported residual symptoms of pain and persistent mechanical irritation (approximately 9.3%) 3 , 10 . The studies do not provide a detailed rationale for this phenomenon, but it is postulated that primarily the associated chondromalacia of the radial head may be the cause of persistent symptoms 1 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation